Innovating Inactive Records Management for Local Bureaucratic Reform: A case study of Kiaracondong sub-district - R. Hari Busthomi Ariffin; Regan Vaughan; Ferdyansyah Wicaksono (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
Effective management of inactive public records is vital for accountability, institutional memory, and service efficiency, particularly at the sub-district level. Many local governments in Indonesia, including Kecamatan Kiaracondong, Bandung City, face systemic challenges due to limited infrastructure, weak policy enforcement, and low organizational commitment. This study examines existing practices and proposes context-sensitive innovations for improving records management as part of bureaucratic reform. A five-month fieldwork employed a qualitative descriptive approach, with data collected through interviews, observations, and document analysis. The analysis followed Miles and Huberman’s interactive model consisting of reduction, display, and verification. The study found that archival practices remain manual, fragmented, and dependent on informal staff knowledge, leading to inefficiency and data vulnerability. Barriers include inadequate storage, absence of trained archival staff, lack of standardized procedures, and the perception of archiving as a secondary task. Despite these challenges, opportunities for reform exist. Low-cost interventions such as spreadsheet-based tracking, standardized manual classification, and internal SOPs, supported by leadership commitment and staff training, provide entry points for gradual transformation. This study contributes by positioning records management as a core element of bureaucratic reform, showing that transformation can begin with incremental, context-specific innovations.